ANALYSIS OF MANGROVE FOREST ECOSYSTEM SUPPORT CAPACITY FOR DEVELOPMENT ECOTOURISM IN ANAK SETATAH VILLAGE, KEPULAUAN MERANTI REGENCY - Romida, Zuwita; Yoswaty, Dessy; Warningsih, Trisla (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
This research was conducted from April 2022 to June 2022 in Anak Setatah Village, Meranti Islands Regency, Riau Province. This study aimed to analyze the carrying capacity of mangrove forest ecosystems, the level of participation, and the perceptions of local communities towards developing mangrove ecotourism in Anak Setatah Village. The method used in this research is the survey method, which is data collection by interview. The data collected consists of primary and secondary data. Preliminary data includes water quality measurement data, carrying capacity (area measurement, length of visit time, physical data of the area), general condition of the research location, questionnaires, and documentation. Secondary data came from journals on mangrove ecotourism potential. Then, the sampling of respondents was determined/selected purposively (purposive sampling). The results showed that the Anak Setatah Village mangrove ecotourism area had several activities: tracking, sitting, photography, and education. The calculation results of the area's carrying capacity in the mangrove ecotourism of Anak Setatah Village are 168 people/day. This means that the maximum number of visitors allowed to do tourist activities in mangrove ecotourism is 168 visitors per day, with the time provided by the manager for traveling being 12 hours. The perception of the Anak Setatah Village community shows promising results, with the IPR category strongly agreeing, and the mean count category is classified into a high category.